Qs. Asy Syura:38 Pada Praktik Sosial: Musyawarah Dalam Komunikasi Para Lintas Tokoh Antar Agama - Shafa, Shafa; Said, Muhammad Nor (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2025)
Abstract: This study examines the application of the principle of shura (consultation) in the Qur’an, particularly based on QS. Asy-Shura: 38, within the context of interfaith communication in Indonesia. Given the country’s religious diversity, social tensions often arise and pose threats to national harmony. This paper argues that shura, as a dialogical and inclusive decision-making method, can serve as a vital tool in fostering tolerance and social cohesion among religious communities. Using a qualitative library research approach, this study analyzes contemporary interpretations of the verse and connects them with real-life practices such as national interfaith summits and digital religious dialogue content. The findings indicate that shura aligns with democratic values and supports the social construction of peace through the processes of externalization, objectivation, and internalization, as theorized by Peter L. Berger. Therefore, this Qur’anic value offers a practical, inclusive, and adaptable framework for interreligious engagement in a pluralistic society.